2019
DOI: 10.3390/atmos10040224
|View full text |Cite
|
Sign up to set email alerts
|

Roadside Moss Turfs in South East Australia Capture More Particulate Matter Along an Urban Gradient than a Common Native Tree Species

Abstract: Urbanisation largely consists of removing native vegetation. Plants that remain interact with air quality in complex ways. Pollutants can be detrimental to plant growth; plants sometimes reduce air quality, yet some species also improve it through phytoremediation. A common pollutant of concern to human health in urban areas is particulate matter (PM), small particles of solid or liquid. Our study compared roadside moss turfs with leaves of a common Australian tree species, Pittosporum undulatum, in their abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Based on the APTI values, we demonstrated that A. saccharinum was moderately tolerant, while P. acerifolia was intermediate. Alotaibi et al [34] reported that the reduction of leaf area was significantly recorded in contaminated areas for P. acerifolia. These findings suggest that the differences in the reduction in leaf areas between tree species at different locations may be due to the availability of leaf surface area and the capacity of leaves for capturing air pollutants [35].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the APTI values, we demonstrated that A. saccharinum was moderately tolerant, while P. acerifolia was intermediate. Alotaibi et al [34] reported that the reduction of leaf area was significantly recorded in contaminated areas for P. acerifolia. These findings suggest that the differences in the reduction in leaf areas between tree species at different locations may be due to the availability of leaf surface area and the capacity of leaves for capturing air pollutants [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the open green spaces dominated by lawns, the settling effect of airborne particulate matter in the air was less hindered, and the airborne particulate matter directly settled on the ground due to the effect of gravity [51]. In addition, mosses showed a higher capability of trapping atmospheric particulate matter than certain trees [52]. Therefore, different vegetation structures had different distributions of airborne particulate matter at different heights of vegetation.…”
Section: The Influence Of Vegetation Structure On the Concentration Of Airborne Particulate Matter At Different Heightsmentioning
confidence: 99%
“…However, the ability to capture PM on leaves is strongly linked to the characteristics of the species (Jouraeva et al 2002;Saebø et al 2012). Plant shape and porosity (Leonard et al 2016), leaf surface morphology, the complexity of the layer of cuticular waxes, the arrangement of stomata and the presence of trichomes on leaves Haynes et al 2019;Prusty et al, 2005) are very important. Urban greenery is able to remove signi cant amounts of pollutants from the air in cities (Kroeger et al 2018;Pugh et al 2012;Vailshery et al 2013;Yang et al 2005), and therefore air phytoremediation is becoming increasingly popular worldwide, especially as it does not involve any tangible costs (Paton-Walsh et al 2019).…”
Section: Introductionmentioning
confidence: 99%